PENGEMBANGAN ASESMEN ALTERNATIF PORTOFOLIO IPA KELAS VIII MATERI SISTEM PEREDARAN DARAH MANUSIA (FMIPA UNNES, 2012)
This study aimed to develop a viable portfolio alternative assessment of science at SMP N 1 Girimarto Wonogiri. The design of this study was Research and Development (R & D). The research data were consisted of the feasibility of portfolio alternative assessment of science, learning activities and learning achievements of students of cognitive, affective and psychomotor. All data were analyzed using descriptive techniques percentage. The results showed that the assessment of the expert of learning assesment and biology content materials indicated that the product was very viable and could be used as an alternative assessment of science, an average score of viability was 93%. The products were effectively utilized by students who were classified as the active and very active in their learning; students’ mastery learning, skills and interests during field tests 1, 2 and 3 were ? 85%, unless the skills of students in the second field test, ? 85%. This study produced the portfolio alternative assessment for human circulatory system that could be used for science subjects at SMP N 1 Girimarto Wonogiri. Penelitian ini bertujuan untuk mengembangkan asesmen alternatif portofolio IPA yang layak digunakan pada mata pelajaran IPA di SMP N 1 Girimarto Wonogiri. Rancangan penelitian ini adalah Research and Development (R&D). Data penelitian berupa kelayakan produk asesmen alternatif portofolio IPA, aktivitas belajar dan hasil belajar siswa aspek kognitif, afektif dan psikomotorik. Semua data penelitian tersebut dianalisis menggunakan teknik deskriptif persentase. Hasil penelitian menunjukkan bahwa pakar asesmen, pakar materi dan guru menyatakan produk yang dikembangkan sangat layak digunakan sebagai alternatif penilaian IPA dengan rata-rata kelayakan 93%. Produk ini efektif digunakan dengan persentase siswa yang aktif dan sangat aktif dalam pembelajaran, ketuntasan belajar siswa, keterampilan dan minat pada uji coba 1, 2 dan 3 sudah ?85%, kecuali keterampilan siswa pada uji coba 2, yaitu ?85%. Simpulan penelitian ini adalah telah dihasilkan asesmen alternatif portofolio IPA materi sistem peredaran darah manusia yang layak digunakan pada mata pelajaran IPA di SMP N 1 Girimarto Wonogiri.